Castles, palaces and manors in Poland – location and current use - Jasion, Angelika; Latosińska, Jolanta (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The aim of this chapter was to identify castles, palaces and manors in Poland and to characterize them in terms of their distribution, state of preservation, ownership relations and current function. The intermediate aim was to present the process of data collection using GIS, evaluation of the collected data and the software used. The research was carried out as part of a student project. On the basis of the register of immovable monuments of the National Heritage Institute, locations and descriptive information for 4 842 castles, palaces and manors in Poland were collected using ArcGIS Online application. Of all classified objects, nearly 53% are manors, 41% palaces, and 6% castles. Most manors are located in the center of Poland. Palaces dominate in the western part of the country. Castles are located mainly in the south-western part of Poland and to a lesser extent in the north. Among the analyzed monuments, 60% are considered as functioning objects. Nearly half of all castles, palaces and manors included in the project are private objects. The most common current function of the analyzed monuments is residential function (18%).